Quality and quantity of serious violent suicide attempts during the COVID-19 pandemic - Maleitzke, Tazio; Zocholl, Dario; Topp, Tobias; Dimitrov-Discher, Annika; Daus, Elly; Reaux, Gabriel; Zocholl, Malin; Conze, Rolf Nicolas; Kolster, Moritz; Weber, Philipp; Fleckenstein, Florian Nima; Scheutz Henriksen, Louise; et al. (Frontiers in Psychiatry, 2022)
Background While repeated shutdown and lockdown measures helped contain the spread of SARS-CoV-2 during the COVID-19 pandemic, social distancing and self-isolation negatively impacted global mental health in 2020 and 2021. Although suicide rates did reportedly not increase during the first months of the pandemic, long-term data, and data on the quality of serious violent suicide attempts (SVSAs) are not available to date. Materials and methods Orthopaedic trauma patient visits to the emergency department (ED), ED trauma team activations, and SVSAs were retrospectively evaluated from January 2019 until May 2021 in four Level-I Trauma Centers in Berlin, Germany. SVSAs were assessed for suicide method, injury pattern and severity, type of treatment, and length of hospital stay. Results Significantly fewer orthopaedic trauma patients presented to EDs during the pandemic (n = 70,271) compared to the control (n = 84,864) period (p = 0.0017). ED trauma team activation numbers remained unchanged. SVSAs (corrected for seasonality) also remained unchanged during control (n = 138) and pandemic (n = 129) periods, and no differences were observed for suicide methods, injury patterns, or length of hospital stay. Conclusion Our data emphasize that a previously reported rise in psychological stress during the COVID-19 pandemic does not coincide with increased SVSA rates or changes in quality of SVSAs.